Drivers of job satisfaction in midwifery—A work design approach. Issue 4 (July 2022) - Mharapara, Tago L.; Staniland, Nimbus; Stadler, Matthias; Clemons, Janine H.; Dixon, Lesley
Abstract: Background: Identifying common factors that influence job satisfaction for midwives working in diverse work settings is challenging. Applying a work design model developed in organisational behaviour to the midwifery context may help identify key antecedents of midwives job satisfaction. Aim: To investigate three job characteristics – decision-making autonomy, empowerment, and professional recognition as antecedents of job satisfaction in New Zealand (NZ) midwives. Methods: Latent multiple regressions were performed on data from Lead Maternity Carer (LMC) midwives n = 327, employed midwives n = 255, and midwives working in 'mixed-roles' n = 123. Findings: We found that professional recognition is positively linked to job satisfaction for midwives in all three work settings. At the same time, decision-making autonomy and empowerment were shown to influence job satisfaction for midwives working as LMCs only. Discussion: Our main finding suggests that the esteem generated from being acknowledged as an expert and valuable contributor by maternity health colleagues is satisfying across all work contexts. Professional recognition encompasses the social dimension of midwifery work and influences midwives job satisfaction. Decision-making autonomy and empowerment are task and relational job characteristics that may not be similarly experienced by all midwives to noticeably influence job satisfaction. Conclusion: Given that job satisfaction contributes to recruitment, retention, and sustainability, our findings show that drivers of job satisfaction differ by midwifery work context. We present evidence to support tailored efforts to bolster midwives job satisfaction, especially where resources are limited.